If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 + 3x + -10 = 52 Reorder the terms: -10 + -10 + 3x + 3x = 52 Combine like terms: -10 + -10 = -20 -20 + 3x + 3x = 52 Combine like terms: 3x + 3x = 6x -20 + 6x = 52 Solving -20 + 6x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 6x = 52 + 20 Combine like terms: -20 + 20 = 0 0 + 6x = 52 + 20 6x = 52 + 20 Combine like terms: 52 + 20 = 72 6x = 72 Divide each side by '6'. x = 12 Simplifying x = 12
| (9x-5)+(4x+29)=26 | | 15n-65=130 | | 3x-10y=-11 | | Ntimes-5=-155 | | -8m^3(3m^2)=0 | | 1/2log13.28 | | 7(3+4x)=-203 | | 3+2k=15 | | X+x-21=87 | | 2.35e^2x=947 | | 22-8/-2 | | f(1)=2x-1 | | 5[3(x+4)-2(1-x)]-x-15=14x+75 | | 1/2=-3/5y-2/3 | | (7x+11)+(16x-38)=77 | | -3+.5c=12 | | F(X)=-(x-1)*2+4 | | 5c+22=-11-10c+15c | | (24x-2)+(25x-8)=118 | | 3n^2+6n+18=0 | | 49m^2-36/25=0 | | 49m^2-36/25= | | 5x-2y=-50 | | 13+.25a=-3 | | m+11=20 | | 8x+6x=10 | | 4x-14*3=x+7*3 | | 2m-7=8-3 | | (7x+26)+(10x-25)=138 | | 15/x=90/7 | | .14x+26=.71x-22 | | 4w+1w+3w-7= |